Xiasangju alleviate metabolic syndrome by enhancing noradrenaline biosynthesis and activating brown adipose tissue - He, Changhao; An, Yongcheng; Shi, Lu; Huang, Yan; Zhang, Huilin; Fu, Wanxin; Wang, Menglu; Shan, Ziyi; Du, Yuhang; Xie, Jiamei; Huang, Zhiyun; Sun, Weiguang; et al. (Frontiers in Pharmacology, 2024)
Metabolic syndrome (MetS) is a clinical condition associated with multiple metabolic risk factors leading to type 2 diabetes mellitus and other metabolic diseases. Recent evidence suggests that modulating adipose tissue to adaptive thermogenesis may offer therapeutic potential for MetS. Xiasangju (XSJ) is a marketed drug and dietary supplement used for the treatment of metabolic disease with anti-inflammatory activity. This study investigated the therapeutic effects of XSJ and the underlying mechanisms affecting the activation of brown adipose tissue (BAT) in MetS. The results revealed that XSJ ameliorated MetS by enhancing glucose and lipid metabolism, leading to reduced body weight and abdominal circumference, decreased adipose tissue and liver index, and improved blood glucose tolerance. XSJ administration stimulated catecholamine biosynthesis, increasing noradrenaline (NA) levels and activating NA-mediated proteins in BAT. Thus, BAT enhanced thermogenesis and oxidative phosphorylation (OXPHOS). Moreover, XSJ induced changes in gut microbiota composition, with an increase in Oscillibacter abundance and a decrease in Bilophila, Candidatus Stoquefichus, Holdemania, Parasutterella and Rothia. XSJ upregulated the proteins associated with intestinal tight junctions corresponding with lower serum lipopolysaccharide (LPS), tumor necrosis factor α (TNF-α) monocyte chemoattractant protein-1 (MCP-1) and interleukin-6 (IL-6) levels to maintain NA signaling transport. In summary, XSJ may alleviate MetS by promoting thermogenesis in BAT to ultimately boost energy metabolism through increasing NA biosynthesis, strengthening intestinal barrier integrity and reducing low-grade inflammation. These findings suggest XSJ has potential as a natural therapeutic agent for the treatment of MetS.